PHILANTHROPY FOR WIDOWS AT ISLAMIC UNIVERSITY-BASED ISLAMIC MICROFINANCE INSTITUTIONS IN MADURA INDONESIA AFTER THE COVID-19 PANDEMIC - Harisah, Harisah; Arief, Zaenal; Dahlan, Rahmat; Rahmawati, Rahmawati; Ahmad, Azlin Alisa (MIZAN: JOURNAL OF ISLAMIC LAW, 2024)
Universities perform a role beyond the enhancement of knowledge in modern society. During the epidemic, however, numerous institutions contributed to the improvement of the community’s economy, and this trend persisted after the outbreak. The financial institutions established on the campuses of Madura’s Islamic universities govern philanthropy as one of the instruments for economic development. Utilizing interviews, observation, and documentation, this research was conducted using a qualitative methodology. The study’s findings indicate that Islamic universities in Madura, through Islamic financial institutions and Islamic boarding schools, contribute to the improvement of the community’s economy from the pandemic to the post-pandemic era through the use of philanthropic instruments, one of which is a widow. Widows are viewed as one of the categories that must be aided by the economy because it is usual for widows, especially those with children, to encounter economic hardships. In Islamic microfinance institutions founded on Islamic colleges in Madura, types of generosity include building houses, supplying meals on a blessed Friday, offering zakat maal and zakat fitrah, waqf in the form of daily necessities, and productive economic forms including capital aid.